(untitled) - Tan, Gerald (Singapore, 1997)
Contents: 1. Concept and Measurement, 2. Population, 3. Foreign Aid,... 14. Conclusion
Keywords: Asia,Châu Á,Asia,Asia,Châu Á; Economic conditions,Điều kiện kinh tế,Social conditions,Social conditions,Điều kiện xã hội